Leadership images in the Korean Church - Kang, G; Hendriks, HJ (Nederduitse Gereformeerde Teologiese Tydskrif, 2015)
This article addresses the membership stagnation problem in the South Korean Church with the hypothesis that leadership pathologies is one of the main reasons for the problems experienced by the Korean Church. The history of the Korean Church is surveyed by examining different leadership images that were applied during specific formative periods. The image of the leader, as charismatic, was very popular in the previous decades and led to spectacular church growth. However, some of the motives that played a role are questionable theologically and in the long run led to mistrust and decline. The article calls for a theological evaluation of both ecclesiology and leadership.